Eksplorasi Nyurat Lontar Bali Pada Mata Kuliah Modul Nusantara Melalui Program Pertukaran MahasiswaMerdeka Di Universitas Pendidikan Ganesha - Andi Reza Pahlawan; Suhardiman Suhardiman; Asmah Amir (Departement of Mathematics Education, 2024)
This research aims to describe the Balinese Nyurat Lontar explored by students in the Nusantara Module course of the Independent Student Exchange program at Ganesha University of Education. This research uses qualitative research. This type of research is descriptive qualitative research. The subjects of this research were tour guides for the Buleleng Museums and Gedong Kirtya. The research instruments used were observation, interviews and documentation. The research results show that studying Nyurat Lontar art in this program gives students a better understanding of Balinese cultural values and local wisdom and broadens their view of the richness of Indonesian art. Learning methods, intercultural interactions, and institutional support are some of the factors that greatly influence the quality of learning in this situation. These findings indicate that the integration of local arts and culture into higher education curriculum is critical to enhancing students' learning experiences and preserving the nation's cultural heritage.